The relationships between pelvic range of motion, step width and performance during an athletic sprint start - Sandamas, P.; Gutierrez-Farewik, E. M.; Arndt, A. (Journal of Sports Sciences, 2020)
The aims of this study were (a) to describe the kinematics underlying the phenomenon of the knee of the swing leg passing medially in front of the athlete during the single push (SP) phase of the block sprint start, and (b) to determine the relationships between block phase pelvis range of motion (RoM), 1st step width and block phase performance. Three-dimensional kinematic data (250 Hz) were collected from eleven competitive sprinters (100 m PB: 11.17 ± 0.41) performing maximal effort block starts. The joint angles of the rear hip with respect to the pelvis and the pelvis segment angles with respect to the laboratory coordinate system were calculated during the block start phase to the end of the 1st stance. A combination of pelvis list and rotation (not hip adduction) was coupled with the thigh of the swing leg moving medially during the SP phase. A very high positive correlation was found between pelvic list RoM and 1st step width (r = 0.799, p = 0.003). No other significant correlations were found. Attempting to reduce pelvic RoM or changing frontal and transverse plane hip joint angles to minimise medial thigh motion is unlikely to lead to an improvement to performance.